Micellization Behavior of Cetyltrimethylammonium bromide in Presence and Absence of Na2SO4 and MgSO4 in Aqueous media - Adhikari, Chom Nath; Shrivastav, G S; Bhattarai, Ajaya (BIBECHANA, 2016)
Viscosity and surface tension measurements of cetyltrimethylammonium bromide (CTAB) in presence and absence of Na2SO4 and MgSO4 in aqueous media are reported. The results showed an increase in viscosity with increase in concentration of cetyltrimethylammonium bromide in presence and absence of salts where as the decrease in surface tension with increase in concentration of cetyltrimethylammonium bromide in presence and absence of salts. The viscosity of CTAB was observed lowest in pure water and increases in presence of MgSO4 and then more increases in presence of Na2SO4 where as the surface tension of CTAB was observed highest in pure water and decreases in presence of Na2SO4 and then more decreases in presence of MgSO4.The critical micelle concentration (cmc) of CTAB decreases in presence of salts in both viscosity and surface tension measurements. The decreasing cmc of CTAB are found to be more in the presence of Na2SO4 in comparison with the presence of MgSO4 for both measurements. The graphs of viscosity versus log[C] and the surface tension versus log[C] are used in determining the critical micelle concentration (cmc).        BIBECHANA 14 (2017) 77-85